Mathematical Model and Matlab Simulation of Strapdown Inertial Navigation System - Wen Zhang; Mounir Ghogho; Baolun Yuan (Modelling and Simulation in Engineering)
Basic principles of the strapdown inertial navigation system (SINS) using the outputs of strapdown gyros and accelerometers are explained, and the main equations are described. A mathematical model of SINS is established, and its Matlab implementation is developed. The theory is illustrated by six examples which are static status, straight line movement, circle movement, s-shape movement, and two sets of real static data.